Bacteroides vulgatus attenuates experimental mice colitis through modulating gut microbiota and immune responses - Liu, Liyun; Xu, Mingchao; Lan, Ruiting; Hu, Dalong; Li, Xianping; Qiao, Lei; Zhang, Suping; Lin, Xiaoying; Yang, Jing; Ren, Zhihong; Xu, Jianguo (Frontiers in Immunology, 2022)
Objectives: Bacteroides vulgatus is one of the predominant Bacteroides species in the human gut and exertes a series of beneficial effects. The aim of this study was to investigate the protective role of B. vulgatus Bv46 in a dextran sodium sulfate (DSS) induced colitis mouse model. Methods: Female C57BL/6J mice were given 3% DSS in drinking water to induce colitis and simultaneously treated with B. vulgatus Bv46 by gavage for 7 days. Daily weight and disease activity index (DAI) of mice were recorded, and the colon length and histological changes were evaluated. The effects of B. vulgatus Bv46 on gut microbiota composition, fecal short chain fatty acids (SCFAs) concentration, transcriptome of colon, colonic cytokine level and cytokine secretion of RAW 264·7 macrophage cell line activated by the lipopolysaccharide (LPS) were assessed. Results: B. vulgatus Bv46 significantly attenuated symptoms of DSS-induced colitis in mice, including reduced DAI, prevented colon shortening, and alleviated colon histopathological damage. B. vulgatus Bv46 modified the gut microbiota community of colitis mice and observably increased the abundance of Parabacteroides, Bacteroides, Anaerotignum and Alistipes at the genus level. In addition, B. vulgatus Bv46 treatment decreased the expression of colonic TNF-α, IL-1β and IL-6 in DSS-induced mouse colitis in vivo, reduced the secretion of TNF-α, IL-1β and IL-6 in macrophages stimulated by LPS in vitro, and downregulated the expression of Ccl19, Cd19, Cd22, Cd40 and Cxcr5 genes in mice colon, which mainly participate in the regulation of B cell responses. Furthermore, oral administration of B. vulgatus Bv46 notably increased the contents of fecal SCFAs, especially butyric acid and propionic acid, which may contribute to the anti-inflammatory effect of B. vulgatus Bv46. Conclusions: Supplementation with B. vulgatus Bv46 serves as a promising strategy for the prevention of colitis.